(untitled) (Contemporary Education and Teaching Research, 2022)
The detection of the first COVID-19 case on 5th March 2020 in Bhutan resulted in the closure of schools across the country. To proceed with the academic curriculum, there was a shift from the regular learning process to e-learning. Lessons were delivered through television and radio which were supplemented with Google classroom, Youtube, and WeChat. Thus, this study explored the effects of e-learning in teaching sixth-grade Bhutanese students during the COVID -19 pandemic. A qualitative study was conducted in one of the primary schools in Bhutan. A Google form was used in collecting data. Thematic analysis was employed to analyze the data collected through semi-structured interviews. The responses collected from 20 participants indicated that e-learning is effective in the development of knowledge and skill, and enhances engagement and self-confidence. E-learning provides opportunities to work independently at their convenience. However, the study also confirms that the implementation of e-learning faces several challenges. Participants felt limited gadgets, lack of knowledge on e-learning, and unfavorable home environment as major obstacles to the success of e-learning. Therefore, stakeholders need to support schools to make e-learning effective in the teaching and learning process.